Compatibility effect of reactive copolymers on polypropylene/polyamide 6 blends from commingled plastic wastes - Hong, S. M.; Hwang, S. S.; Choi, J. S.; Choi, H. J. (WILEY, 2006)
We report the compatibility effect on a recycled polypropylene/nylon (75/25) blend processed with reactive copolymers on the basis of morphological, mechanical, and rheological characteristics. Via a scanning electron microscopy investigation, we found improved surface morphologies with regular and fine domains in a recycled polypropylene/nylon (75/25) blend compatibilized with copolymers containing maleic anhydride as a reactive functional group [styrene-(ethylene/butylene)-styrene-graft-maleic anhydride copolymer and polypropylene-graft-maleic anhydride]. Large increases in both the mechanical and rheological properties with the addition of the styrene-(ethylene/butylene)-styrene-graft-maleic anhydride copolymer could be interpreted with respect to a specific structure at the interface, showing a strong interfacial adhesion between recycled polypropylene and nylon. To confirm the existence of this structure, we used various dynamic rheological parameters: the Cox-Merz rule, storage modulus, and phase angle. (c) 2006 Wiley Periodicals, Inc.
Keywords: MECHANICAL-PROPERTIES; TERNARY BLENDS; RHEOLOGY; POLYETHYLENE; VISCOELASTICITY; MISCIBILITY; MORPHOLOGY; BEHAVIOR; BINARY; PHASE